Ecomuseum of the Quilombola Community of São Pedro de Cima - Lucia Pires Menezes, Maria; Francisco Leopoldo, Dayana; de Castro Morais, Victor (Seven Editora, 2023)
The ECOMUSEU project of the Quilombola Community of São Pedro de Cima was designed and organized as a university extension project with professors and students of the Geography course at the Federal University of Juiz de Fora. The starting point of this project arises from a field work carried out in 2007 in the discipline of Agrarian Geography, from then on, a web is built with the community and it started to present demands that gave rise to this extension project. The quilombola community of São Pedro de Cima is an extremely rich geographical sociocultural reality, and this reality is one of the reasons for carrying out this extension work. . The project has its relevance for providing the interrelation between the different actors of the local community and with the institutions present, in particular the public school. Therefore, this work aims to contribute to discussions mainly economic and sociocultural about the Brazilian agrarian processes that were responsible for the emergence of excluded territories and that today interact with the agro-export model fostered by Brazilian policy. DOI: 10.56238/pacfdnsv1-053